Filled Skutterudites for Broadband Saturable Absorbers. Issue 11 (13th April 2017) - Lee, Junsu; Yu, Byung‐Kyu; Jhon, Young In; Koo, Joonhoi; Kim, Sung Jin; Jhon, Young Min; Lee, Ju Han
Abstract : Filled skutterudites (FSs), which are known to be good thermoelectric materials, have been intensively investigated in the field of condensed matter physics in the past decades, due to their large variety of electronic and magnetic properties. However, to the best of the authors' knowledge, there has been no previous investigation of the optical properties of FSs. The nonlinear optical saturable absorption property of FSs is investigated in this work for the first time, and the results are reported here. More specifically, Co4 Sb12 is chosen as a binary skutterudite system, and indium ions are added as a filling element to form a FS of In0.2 Co4 Sb12 . The material properties are systematically investigated using a series of measurements. Density functional theory calculations of the electronic band structures of InCo4 Sb12 and In0.25 Co4 Sb12 are conducted for better understanding of their energy band structures. It is also demonstrated that a broadband saturable absorber (SA) that can simultaneously operate at 1.5 and 1.9 µm can readily be implemented by depositing particles of In0.2 Co4 Sb12 onto fiber ferrules. The efficacy of the prepared SA is tested by incorporating the device into rare earth ion‐doped fiber ring cavities, to show its capability for both 1.5 and 1.9 µm operation. Abstract : This is the first time demonstration of the nonlinear optical properties of filled skutterudites (FSs), which are known to be good thermoelectric materials. The nonlinear saturable absorption in an FS of In0.2 Co4 Sb12 is investigated theoretically and experimentally. An FS‐based saturable absorber that can simultaneously operate at 1.5 and 1.9 μm, is fabricated and tested within rare earth ion‐doped fiber ring cavities.